Comparison of Biological Habits and Leisure Time Activities Among Native and Non-Native Students in Universities of Kerman Province - Naseri, Sahra; Afrooz, GholamAli; Ghanbarihashemabady, Bahramali; Sajjadi Anari, Seyed Saeid (Mental Health and Lifestyle Journal, 2026)
The present study was conducted with the aim of comparing the level of biological habits and the ways of spending leisure time among native and non-native students in universities of Kerman Province. The study was applied in purpose and descriptive–comparative (ex post facto) and cross-sectional in method. The statistical population included all associate to doctoral students of universities in Kerman Province during the 2024–2025 academic year. From this population, 360 participants (180 native and 180 non-native students) were selected through convenience sampling. The data collection instrument was the Lifestyle Questionnaire, whose overall reliability was obtained at 0.87 using Cronbach’s alpha. Data were analyzed using SPSS software and the independent t-test. The results indicated that there was a significant difference between native and non-native students in some components of lifestyle. Native students had higher mean scores in the dimensions of “social health,” “spiritual health,” and “disease prevention,” whereas non-native students performed better in the components of “exercise and physical well-being” and “group leisure activities.” Furthermore, the overall mean of biological habits among native students was higher than that of non-native students, although the difference in the total lifestyle score was not statistically significant (p > 0.05). The findings suggest that differences in living conditions and access to supportive resources can influence students’ biological patterns and leisure time behaviors. University-level planning to promote a healthy lifestyle—particularly among non-native students—can play a crucial role in preventing individual and social harm and in improving students’ mental health.